Aluminum exposure in premature babies related to total parenteral nutrition and treatments - Emre Aşut; Nilgün Köksal; Bayram Ali Dorum; Hilal Özkan (The Turkish Journal of Pediatrics)
This study aimed to measure aluminum contamination of parenteral nutrition (PN) solutions and aluminum contents of parenteral products given to newborn infants for nutrition or treatment. In this study, the aluminum content of the first products used to prepare PN solutions for premature neonates, of the final parenteral products prepared therefrom, and of the parenteral drugs frequently used in newborn units was measured using the inductively coupled plasma mass spectrometry. The aluminum contamination of all parenteral nutritional products evaluated, except for one, was detected to be over the recommended doses. Of all the first products analyzed within the scope of the study, trace-element preparation, preparation containing fat-soluble vitamins, 20% dextrose solution, calcium gluconate ampoule and sodium phosphate ampoule indicated high aluminum contamination. The total aluminum content of the prepared final products was identified to be at least 40% higher than the total aluminum content of the ingredients added to the compound. Accordingly, the minimum amount of aluminum content was measured as 233 μg/kg/day in nutrition solutions prepared for a baby weighing 1,000 g. Contamination was detected in 9 of the 18 drugs evaluated. This study indicated that the rate of aluminum exposure of the premature babies receiving parental nutrition is still much higher than the safe doses recommended as 5 µg/kg/day by the FDA. Products with lower aluminum content should be preferred in the care of premature infants.